I composti Nome-Nome coordinati e subordinati nel lessico sportivo italiano come prova delle tendenze in atto nell’italiano contemporaneo - Szemberska, Anna (Studia Romanica Posnaniensia, 2013)
The compounding is a fundamental process of word formation and its importance to our understanding of language is crucial. The study of compounds for the last few years has been at the centre of attention in such areas of linguistics as computational approaches, psycholinguistics and language acquisition. Linguists advanced hypotheses not only regarding the construction of compounds, but also where they fit into the model of grammar. The paper attempts to answer some basic questions pertaining to lexical creativity in nominal compounding in Italian sports column. These include the definition of the concept, the types of noun-noun compounds in Modern Italian and a brief comparison of these types.